The Routledge introduction to Canadian fantastic literature - Weiss, Allan, 1956- (New York : Routledge, Taylor & Francis Group, 2021)
"This study introduces the history, themes, and critical responses to Canadian fantastic literature. Taking a chronological approach, this volume covers the main periods of Canadian science fiction and fantasy from the early nineteenth century to the first decades of the twenty-first century. The book examines both the texts and the contexts of Canadian writing in the fantastic, analyzing themes and techniques in novels and short stories, and looking at both national and international contexts of the literature's history. This introduction will offer a coherent narrative of Canadian fantastic literature through analysis of the major texts and authors in the field and through relating the authors' work to the world around them"--
OCLC-licensed vendor bibliographic record.
Keywords: Fantasy fiction, Canadian -- History and criticism; LITERARY CRITICISM / General